Perbandingan Unsur Batin Kumpulan Puisi Luka Kata Karya Candra Malik dengan Kumpulan Puisi Menyelamimu Karya Agung Setiawan S. - Inda Puspita Sari; Agung Nugroho; Septa Mila Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this research is to describe the comparison of the inner elements of the poetry collection Luka Kata by Candra Malik and the collection of the poetry Diving by Agung Setiawan.S. The research method used is descriptive qualitative method with a literature approach. Comparing Candra Malik's Luka Kata poetry collection and Agung Setiawan S. It can be compared that in the study of these two collections of poetry that the theme of poetry leads to the world of love and all its consequences. In terms of taste, these two collections of poetry also express feelings of longing and disappointment that are implied and expressed through their lines. In terms of tone and atmosphere, these two collections of poetry are so different. In the collection of poetry Luka Kata by Candra Malik, the tone and atmosphere that are depicted is more of an advising tone with a touching atmosphere. Whereas in the collection of the poetry Diving by Agung Setiawan S, the tone depicted is more of a mocking tone with a sad atmosphere. However, in terms of the mandate, these two collections of poetry have something in common again and again. The mandate in this collection of poems provides advice on the world of romance (romance) and all things related to joy and sorrow for those who enter that world. Based on the research results, it can be concluded that the collection of poetry Luka Kata by Candra Malik and the collection of the poetry Diving by Agung Setiawan has many differences in terms of the language of conveying the inner elements. Keywords: Comparison, Poetry Collection, Mental Elements.